Singlet-assisted diffusion-NMR (SAD-NMR): extending the scope of diffusion tensor imaging via singlet NMR - Melchiorre, Giulia; Giustiniano, Francesco; Rathore, Sundeep; Pileio, Giuseppe (Frontiers in Chemistry, 2023)
Long-lived nuclear singlet order methods are here combined with diffusion tensor imaging with the purpose of characterizing the full diffusion tensor of molecules that freely diffuse in large pores of up to the millimeter. Such sizes are out-of-reach to conventional diffusion tensor imaging because of the limitations imposed by the relaxation decay constant of the longitudinal magnetization. A singlet-assisted diffusion tensor imaging methodology able to circumvent such limitations is discussed and the new possibilities it offers are demonstrated through simulation and experiments on plastic phantoms containing cylindrical channels of onemillimeter diameter.